Management learning for construction professionals. Inquires benchmarks and experiences from Poland, United Kingdom and Portugal - Kazimierz Cieszyński; Andrzej Minasowicz; José Cardoso Teixeira (Technological and Economic Development of Economy, 2006)
Management qualification of construction staff is an essential step towards Polish market development. Inquiries revealed the framework for qualification requirements that led to the establishment of a matrix of learning subjects. Learning requirements followed from that matrix and allowed for the definition of management learning profiles for construction professionals. These profiles have been compared to frameworks from other European institutions and lay the basis for defining training structures and learning programmes.